2017
DOI: 10.1515/rjdnmd-2017-0040
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M, Interleukin-6, Glucometabolic Parameters and Lipid Profile in Hypertensive Patients with Prediabetes and Type 2 Diabetes Mellitus

Abstract: Background and aims:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Increase of the circulating levels of OSM in subjects with coronary artery disease, heart failure, pulmonary arterial hypertension, atrial fibrillation has been demonstrated in a number of experimental and clinical studies (23,(26)(27)(28). It became obvious that the data obtained for the role of OSM in heart function depend on the type of the pathological condition and are often quite contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Increase of the circulating levels of OSM in subjects with coronary artery disease, heart failure, pulmonary arterial hypertension, atrial fibrillation has been demonstrated in a number of experimental and clinical studies (23,(26)(27)(28). It became obvious that the data obtained for the role of OSM in heart function depend on the type of the pathological condition and are often quite contradictory.…”
Section: Discussionmentioning
confidence: 99%